2015
DOI: 10.1039/c5py00983a
|View full text |Cite
|
Sign up to set email alerts
|

Precise synthesis of thermoreversible block copolymers containing reactive furfuryl groups via living anionic polymerization: the countercation effect on block copolymerization behavior

Abstract: The anionic block copolymerization of 4,4'-vinylphenyl-N,N-bis(4-tert-butylphenyl)benzenamine (A) with furfuryl isocyanate (B) was carried out using potassium naphthalenide (K-Naph) in tetrahydrofuran at −78 and −98°C to prepare well-defined block copolymers containing furan groups for the formation of thermoreversible networks via a Diels-Alder (DA) reaction. While no block copolymerization was observed in the absence of sodium tetraphenylborate (NaBPh 4 ) due to side reactions, well-defined poly-copolymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…However, from the figure it was observed that the exotherm was broad as well as weak, which might be due to the fast cooling of the sample that hinders the accomplishment of the DA reaction. In several previous reports, this phenomenon [ 46,47 ] has already been reported. Table S1 (Supporting Information) summarizes the results obtained from the DSC analysis of the functionalized XNBR and DA‐crosslinked XNBR.…”
Section: Resultssupporting
confidence: 60%
“…However, from the figure it was observed that the exotherm was broad as well as weak, which might be due to the fast cooling of the sample that hinders the accomplishment of the DA reaction. In several previous reports, this phenomenon [ 46,47 ] has already been reported. Table S1 (Supporting Information) summarizes the results obtained from the DSC analysis of the functionalized XNBR and DA‐crosslinked XNBR.…”
Section: Resultssupporting
confidence: 60%
“…Kang et al recently reported the formation of thermoreversible block copolymers containing pendant triphenylamine (A) and furan (B) by anionic polymerization, resulting in an A–B–A block copolymer . Upon addition of a bis maleimide crosslinker at 50 °C a crosslinked polymer was formed, as evidenced by DSC, which showed a large increase in T g due to reduction in chain mobility.…”
Section: Diels‐alder and Retro‐diels‐alder Reactionmentioning
confidence: 99%
“…To date, most of the reported DC polymers that are based on the Diels‐Alder reaction, rely on furan as the diene . Both the groups of Bapat et al and Barthel et al relied on a thermoreversible Diels‐Alder reaction to control the crosslinking of micelles.…”
Section: Diels‐alder and Retro‐diels‐alder Reactionmentioning
confidence: 99%
“…Based‐on the previous successful block copolymerization with HIC, another isocyanate derivative, furfuryl isocyanate (FIC), was used in the second stage of polymerization in the presence of excess NaBPh 4 at −98 °C . The undesired side reactions did not occur during polymerization, leading to well‐defined block copolymers, poly(VPTBTPA)‐ b ‐poly(FIC), with controlled M n (18 700–19 500 g mol ‐1 ) and narrow MWD ( M w / M n = 1.08–1.17).…”
Section: Functional Block Copolymers From Triphenylamine Carbazole mentioning
confidence: 99%